Challenges Faced by FKIP Students at Lambung Mangkurat University in Optimizing Affiliate Marketing - Yudya Ananda; Ersis Warmansyah Abbas; M. Ridha Ilhami; Sovia Husni Rahmia; Sigit Triyono (The Kalimantan Social Studies Journal, 2025)
In recent years, affiliate marketing has emerged as a potential opportunity for students, particularly those at the Faculty of Teacher Training and Education at Lambung Mangkurat University, to earn additional income amid rising tuition fees and living costs. However, practice in the field shows that students often face a number of obstacles that can reduce the effectiveness and earning potential of this activity. This study focuses on analyzing the various challenges faced by students in utilizing affiliate marketing, both those arising from external factors such as changes in commission policies and internal factors such as time management and motivation. The research was conducted using qualitative methods through direct observation, in-depth interviews, and documentation to explore students' experiences in more detail in undergoing affiliate marketing programs. The findings reveal that uncertainty in commission policies, low motivation, and difficulties in balancing academic obligations and marketing activities are the main obstacles. With a deeper understanding of these challenges, it is hoped that students can formulate more effective strategies to overcome them, so that affiliate marketing can truly be maximized as a meaningful source of additional income.